Radiofrequency thermocoagulation of Gasserian ganglion in trigeminal neuralgia - Rulewska, Natalia Maria; Grabowski, Filip; Neska, Dagmara; Siemko, Jakub; Prystacka-Szar, Dominika; Stadler-Szajda, Justyna; Czyżnikiewicz, Adrianna; Stołowski, Wenancjusz; Bujak, Magdalena; Waśniowska, Magdalena; et al. (Journal of Education, Health and Sport, 2025)
Introduction: Trigeminal neuralgia (TN) is a form of neuropathic pain that targets the fifth cranial nerve, leading to intense facial pain that can significantly impact one’s quality of life. This condition typically manifests as recurring episodes of sharp, unilateral pain along one or more branches of the trigeminal nerve.The exact mechanism of trigeminal neuralgia remains largely unknown. Most pain attacks are triggered by certain stimuli in the areas served by the trigeminal nerve. One possible treatment approach for trigeminal neuralgia is radiofrequency thermocoagulation. Aim: The aim of this article is to explore the underlying mechanisms of trigeminal neuralgia and assess the effectiveness of treating it through radiofrequency thermocoagulation of the Gasserian ganglion. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the searchterms encompassing the following keywords: trigeminal neuralgia / Gasserian ganglion radiofrequency thermal therapy/ radiofrequency thermal coagulation/ radiofrequency trigeminal rhizotomy/ trigeminal neuralgia mechanism. Conclusion: The exact mechanisms behind trigeminal neuralgia are still unclear, but several theories suggest that factors such as inflammation, ion channel dysfunction, neuroinflammatory conditions, or bioresonance issues may be involved. Radiofrequency Thermocoagulation (RFT) has proven to be an effective option for easing pain in individuals suffering from Trigeminal Neuralgia. Research indicates that RFT not only significantly reduces pain initially but also provides a prolonged period of relief post-procedure. The temperature achieved during radiofrequency treatments is a key factor in determining the effectiveness of RFT.